Behavior of Double-Web Angles Beam to column connections - Al-Fakih, Kamal Ahmed; Chin, Siew Choo; Doh, Shu Ing (IOP Publishing, 2018)
This paper contains the study performed on the behavior of double-web angles by using finite element analysis computer package known as "Abaqus". The aim of this present study was simulating the behavior of double-web angles (DWA) steel connections. The purpose of this article is to provide the basis for the fastest and most economical design and analysis and to ensure the required steel connection strength. This study, started used review method of behavior of steel beam-to-column bolted connections. Two models of different cross-section were examined under the effect of concentrated load and different boundary conditions. In all the studied case, material nonlinearity was accounted. A sample study on DWA connections was carried out using both material and geometric nonlinearities. This object will be of great value to anyone who wants to better understand the behavior of the steel beam to column connection. The results of the study have a field of reference for future research for members of the development of the steel connection approach with simulation model design.